Effectiveness of respiratory management for mechanical ventilator weaning in traumatic spinal cord injury patients with prolonged ventilation - Pukovisa Prawiroharjo; Julia Remi Chandra; Diatri Nari Lastri; Ramdinal Aviesena Zairinal; Adre Mayza; Yetty Ramli; Maula N. Gaharu; Riyadh Firdaus; Peggy; Yoshua Viventius (Romanian Journal of Neurology, 2024)
Background. Traumatic spinal cord injury is a medical condition which often results in disability and mortality. The most common lesion was cervical level, which is around 60-75% of all cases, where at this level there is a risk of respiratory problems which often require mechanical ventilation. Case report. In the case discussed, a 28-years-old male was referred from other hospital with traumatic cervical spinal cord injury (C5-C6) ASIA score A with a history of falling from a height of 3 meters. The patient underwent decompressive laminectomy on the tenth day of onset, followed by mechanical ventilation. During treatment, the patient received pharmacological therapy, tracheostomy, acupuncture, physiotherapy, and neuromuscular electrical stimulation for ventilator weaning. The patient was hospitalized for 66 days, with mechanical ventilation duration for 32 days. Conclusions. Factors that can influence the duration of ventilation weaning are the level and severity of spinal cord injury, time of transfer to a health facility, and complications related to ventilator installation. Multidisciplinary management, including pharmacological, physiotherapy, acupuncture, surgical, neuromuscular electrical stimulation, can increase the chances and decreasing the duration of mechanical ventilation, and reducing complications related to spinal cord injury and prolonged ventilation.